Seamless Integration of Conducting Hydrogels in Daily Life: From Preparation to Wearable Application - Imani, K.B.C.; Dodda, J.M.; Yoon, J.; Torres, F.G.; Imran, A.B.; Roshan Deen, G.R.; Al-Ansari, R. (John Wiley and Sons, 2024)
Conductive hydrogels (CHs) have received significant attention for use in wearable devices because they retain their softness and flexibility while maintaining high conductivity. CHs are well suited for applications in skin-contact electronics and biomedical devices owing to their high biocompatibility and conformality. Although highly conductive hydrogels for smart wearable devices are extensively researched, a detailed summary of the outstanding results of CHs is required for a comprehensive understanding. In this review, the recent progress in the preparation and fabrication of CHs is summarized for smart wearable devices. Improvements in the mechanical, electrical, and functional properties of high-performance wearable devices are also discussed. Furthermore, recent examples of innovative and highly functional devices based on CHs that can be seamlessly integrated into daily lives are reviewed.
Keywords: Wearable computer; Self-healing hydrogels; Wearable technology; Flexibility (engineering); Nanotechnology; Biocompatibility; Electronics; Computer science; Materials science; Embedded system; Engineering; Electrical engineering; https://purl.org/pe-repo/ocde/ford#2.02.01